2019
DOI: 10.1002/rmv.2046
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNAs: Novel regulators of virus‐host interactions

Abstract: Long noncoding RNAs (lncRNAs) represent a key class of cellular regulators, involved in the modulation and control of multiple biological processes. Distinct classes of lncRNAs are now known to be induced by host cytokines following viral infections.Current evidence demonstrates that lncRNAs play essential roles at the hostpathogen interface regulating viral infections by either innate immune responses at various levels including activation of pathogen recognition receptors or by epigenetic, transcriptional, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 119 publications
(137 reference statements)
0
30
0
Order By: Relevance
“…They are mainly classified into short‐chain (including siRNA, miRNA, piRNA) and long‐length (long noncoding RNA, lncRNA) according to their length . LncRNA is a type of RNA which is longer than 200 in length and does not have the function of encoding protein . Initially, lncRNAs are thought to be RNAs that have no biologically function.…”
Section: Introductionmentioning
confidence: 99%
“…They are mainly classified into short‐chain (including siRNA, miRNA, piRNA) and long‐length (long noncoding RNA, lncRNA) according to their length . LncRNA is a type of RNA which is longer than 200 in length and does not have the function of encoding protein . Initially, lncRNAs are thought to be RNAs that have no biologically function.…”
Section: Introductionmentioning
confidence: 99%
“…The potential functions of differentially expressed mRNAs, miRNAs and circRNAs were anlyzed and were closely related to inflammatory response [16]. Recently, increasing studies have indicated that lncRNAs play important roles in inflammatory response [17][18][19][20]. Therefore, we proposed that lncRNAs also might participate in regulating inflammatory response during TGEV infection.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years considerable attention has been placed investigating the role of non-coding RNA in viral infections. Nucleotide sequences longer than 200 are usually considered as long non-coding RNA and have been found to be important both in host cell response and virus defense mechanisms (15,16). In addition small non-coding RNA's (RNAi) have a variety of formulations including both singlestranded RNA (micro (mi)RNA) (17) and double-stranded RNA (siRNA).Their actions may be promulgated either in cis or in trans (sfRNA) (18).…”
Section: Discussionmentioning
confidence: 99%